2017
DOI: 10.1101/180513
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ventral hippocampal CA1 and CA3 differentially mediate learned approach-avoidance conflict processing

Abstract: 1The ventral hippocampus is thought to play a key role in the resolution of approach-avoidance 2 conflict, a scenario that arises when stimuli with opposing valences are present simultaneously. 3Little is known, however, about the contributions of specific hippocampal sub-regions in this 4 process, a critical issue given the functional and anatomical heterogeneity of this structure. Using 5 a non-spatial cue-based paradigm in rats, we found that transient pharmacological inactivation of 6 ventral CA1 produced … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
23
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 61 publications
7
23
2
Order By: Relevance
“…Animals were first trained to associate three distinct visuotactile cues with either appetitive, aversive, or neutral outcomes in a 3‐arm Y‐maze and were subsequently presented with a conflict cue, composed of positive and negative cues, in one arm and a neutral cue in another arm. It was found that transient inactivation of the ventral CA3 subfield potentiated approach behavior toward the conflict stimulus, akin to the effects of whole ventral HPC lesions in previous work (Schumacher et al, ), whereas inactivation of the ventral CA1 led to greater avoidance (Schumacher et al, ). This work suggests that the ventral HPC can be further divided into separate motivational circuits when approach–avoidance conflict is evoked, possibly mediated through differential connections to other subcortical structures.…”
Section: Introductionsupporting
confidence: 58%
See 4 more Smart Citations
“…Animals were first trained to associate three distinct visuotactile cues with either appetitive, aversive, or neutral outcomes in a 3‐arm Y‐maze and were subsequently presented with a conflict cue, composed of positive and negative cues, in one arm and a neutral cue in another arm. It was found that transient inactivation of the ventral CA3 subfield potentiated approach behavior toward the conflict stimulus, akin to the effects of whole ventral HPC lesions in previous work (Schumacher et al, ), whereas inactivation of the ventral CA1 led to greater avoidance (Schumacher et al, ). This work suggests that the ventral HPC can be further divided into separate motivational circuits when approach–avoidance conflict is evoked, possibly mediated through differential connections to other subcortical structures.…”
Section: Introductionsupporting
confidence: 58%
“…In the arm with the neutral cue, the animals did not experience any outcomes. Previous studies from our laboratory had demonstrated that these specific schedules and magnitudes of sucrose reward and shock facilitate the development of conditioned approach and avoidance to the appropriate cues without inducing generalized fear of the apparatus and freezing responses to the aversive cue, and results in control animals spending roughly equal times in the conflict and neutral arms during the conflict test (Hamel, Thangarasa, Samadi, & Ito, ; Schumacher et al, , ). The order of arm presentation was varied daily to prevent the animals associating the outcomes with the sequence of arm presentation.…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations